Impact of hyperthermia on pharmacokinetics of intraperitoneal mitomycin C in rats investigated by microdialysis. Issue 6 (17th December 2013) - Sørensen, Olaf; Andersen, Anders Mikal; Kristian, Alexandr; Giercksky, Karl‐Erik; Flatmark, Kjersti
<x xml:space="preserve">Abstract</x> Background and Objectives Patients with peritoneal surface malignancies are treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy, commonly using mitomycin C (MMC). The purpose of this study was to investigate impact of hyperthermia on pharmacokinetics of intraperitoneal MMC. Methods In 14 athymic nude male rats, microdialysis (MD) probes were implanted in jugular vein (V), hind leg muscle (M) and extraperitoneal space (XP). Probes were calibrated by retrodialysis. Intraperitonal chemotherapy perfusion (IPEC) was administered over 90 min with MMC 5 mg/kg and saline 0.9% 500 ml/kg at 35 and 41°C, defining the normothermic (NG) and hyperthermic groups (HG), respectively. MD and peritoneal perfusion fluid (PPF) samples were collected at 10 min intervals to determine MMC concentration. Results Time–concentration curves were virtually parallel between temperature groups, with equal peak concentrations (µM) of 0.3 (V), 0.7 (XP) and 0.3 (M). The following area under time–concentration curve (AUC) ratios were calculated: AUC PPF/AUC V were 69 in NG and 79 in HG (P = 0.54); AUC XP/AUC V were 2.7 in NG and 2.6 in HG (P = 0.90). Conclusions IPEC provides high intraperitoneal MMC concentration and increased bioavailability in extraperitoneal tissue, combined with low systemic absorption. Hyperthermia at 41°C did not modify MMC pharmacokinetics. J. Surg. Oncol. 2014 109:521–526. © 2013 Wiley Periodicals, Inc.